The Importance of Public-Private Partnership Models in the Development of Railway Stations (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
This article provides information on the essence of public-private partnership, the need for its use in railway passenger transport, the advantages of the concession form of PPP and its various models.